Factors influencing sales people’s performance: a study of mobile service providers in Bangladesh - Talukder, Kamarul Islam; Jan, Muhammad Tahir (Allied Business Academies, 2017)
Mobile service provider markets are a standout amongst the most unstable market environments because of expanded rivalry and change in the market. Thus, the developing concern requires the marketers to entirely look at client purchasing choice and satisfying procedure. On this basis, the purpose of the study is to more focus on the factors that influence sales people’s performance in mobile phone service providers. This paper used structural equation modelling (SEM) approach to test the research model. A primary data was collected using self-administered questions from mobile phone service operator in Dhaka city. The sample included 262 active sales people using a purposive sampling technique. The results revealed that intrinsic motivation, extrinsic motivation, organizational commitment and compensation had a significant relationship with sales people’s performance, whilst, job satisfaction has not significant impact on sales people’s performance. This study contributes a foundation for future research in achieving the objective of this study and fast developing mobile phone service industry.